Beyond 1.0 W cm−2 Performance without Platinum: The Beginning of a New Era in Anion Exchange Membrane Fuel Cells. Issue 15 (1st January 2018) - Omasta, Travis J.; Peng, Xiong; Miller, Hamish A.; Vizza, Francesco; Wang, Lianqin; Varcoe, John R.; Dekel, Dario R.; Mustain, William E.
Abstract : This work reports a high power, stable, completely Pt-free anion exchange membrane fuel cell (AEMFC) comprised of highly active catalysts – Pd-CeO2 /C at the anode and PdCu/C alloy at the cathode for the hydrogen oxidation and oxygen reduction reactions, respectively. The resulting AEMFC shows outstanding performance, reaching a peak power density of 1 W cm −2, twice the value of the best performance for Pt-free cells reported in the literature to date. The AEMFC also shows a low voltage degradation rate when operated continuously for more than 100 h at a constant 0.5 A cm −2, with a voltage degradation rate of only 2.5 mV h -1, which is excellent when compared to nearly all of the AEMFCs reported in the literature to date. This combination of high performance and high stability in the absence of Pt-based catalysts represents a significant landmark in the progress of the AEMFC technology.